The Effectivity of Virtual Education Toward Knowledge and Perception About COVID-19 Vaccine Among Pregnant Women - Saridewi Pujiastuti N; Dewi Marfuah (Risenologi, 2022)
Pregnant women are a high-risk population in the occurrence of COVID-19 transmission, some cases present with severe symptoms to death. In recently, the number of pregnant women who have received the vaccination are fewer than pregnant women who have not receive it. Knowledge and perceptions of pregnant women are important in preventing COVID-19, one of which is by vaccinating. Virtual education was chosen because it was considered relevant and possible in a pandemic. Purpose of this research is to identify the effectiveness of virtual education on knowledge and perceptions of pregnant women about the COVID-19 vaccine. The method was Quasy-Experimental quantitative research with Two Group Pre-Post test design, on 70 samples with inclusion criteria: pregnant women who have not been vaccinated, can read and have a smartphone. The questionnaire consists of knowledge and perception  about COVID-19 vaccine by online. Virtual education about COVID -19 vaccine was given to the treatment group. The data analysis using T-test and ANCOVA. The results shows that the respondents was 30.09 years old (SD = 4,794), 50% wiveshouse, 31,4% had been exposed to COVID-19, and 84.3% had no comorbidities. There is a significant difference in the pre and post-test scores in the intervention group with the results of the Paired T-Test (p-Value 0.000) and the ANCOVA test (p-Value 0.000). The conclusion show that virtual education is effective to increase knowledge and perceptions of pregnant women about the COVID-19 vaccine. Virtual education can be an alternative method during the pandemic to promote health about COVID-19 vaccination.